1997
DOI: 10.1073/pnas.94.12.6438
|View full text |Cite
|
Sign up to set email alerts
|

A role for Sp and nuclear receptor transcription factors in a cardiac hypertrophic growth program

Abstract: During cardiac hypertrophy, the chief myocardial energy source switches from fatty acid ␤-oxidation (FAO) to glycolysis-a reversion to fetal metabolism. The expression of genes encoding myocardial FAO enzymes was delineated in a murine ventricular pressure overload preparation to characterize the molecular regulatory events involved in the alteration of energy substrate utilization during cardiac hypertrophy. Expression of genes involved in the thioesterification, mitochondrial import, and ␤-oxidation of fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
131
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(141 citation statements)
references
References 52 publications
6
131
0
2
Order By: Relevance
“…These results from the 26-week experiment in vivo suggest that WY-14,643 directly increases the amount of protein in rat hearts, because it had this effect on H9c2 cells, a cardiomyocyte cell line. Sack et al (1997) reported that the amount of nuclear PPAR is decreased in a hypertrophied heart. The same group also reported that PPAR is deactivated during the -adrenergic agonistinduced hypertrophic growth in an overexpressed recombinant PPAR system (Barger et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results from the 26-week experiment in vivo suggest that WY-14,643 directly increases the amount of protein in rat hearts, because it had this effect on H9c2 cells, a cardiomyocyte cell line. Sack et al (1997) reported that the amount of nuclear PPAR is decreased in a hypertrophied heart. The same group also reported that PPAR is deactivated during the -adrenergic agonistinduced hypertrophic growth in an overexpressed recombinant PPAR system (Barger et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Nothing, however, is known with regard to the potential role of PPAR in the pathology of cardiac tissue (Bishop-Bailey, 2000). Sack et al (1997) reported that the amount of nuclear PPAR decreases in the hypertrophied mouse heart. Barger et al (2000) reported that PPAR is deactivated by several times, leading to diminished capacity for myocardial lipid and energy homeostasis duringadrenergic agonist-induced cardiac hypertrophic growth in rat neonatal cardiac myocyte.…”
Section: Introductionmentioning
confidence: 99%
“…In conditions of pressure-induced cardiac hypertrophy, PPAR-␣ is downregulated, resulting in reversion of the heart to the fetal pattern of glucose and lactate substrate utilization (4,74). Diminished cardiac FAO and increased utilization of glucose has been found in studies of both murine (73) and human (19) cardiac hypertrophy. This switch reduces the oxygen requirement of the heart to produce ATP, which is higher per mole of fatty acid substrate oxidized than for glucose (94).…”
Section: Ppar-␣ and The Heartmentioning
confidence: 99%
“…Specifically, SIRT1 deacetylates PPAR␥ coactivator 1␣ (PGC-1␣), a critical regulator of mitochondrial oxidative metabolism and the maintenance of glucose, lipid, and energy homeostasis, increasing its transcriptional activity. 176 In human and rat CHF 177,178 and in murine models of pressure overload, 179,180 metabolic dysregulation occurs in the heart that is characterized by marked reduction in mitochondrial oxidative metabolism rates with a concomitant shift to increased glucose utilization placing PGC-1␣ in a key position to mediate this process. In fact, the loss of PGC-1␣ results in early symptoms of heart failure in mice.…”
Section: Resveratrolmentioning
confidence: 99%